Fetuin-A as Metabolic Biomarker in Patients at Higher Risk of Heart Failure - Berezin, A. A.; Poliasny, V. A.; Kovalevskaya, L. A.; Ivanchenko, S. A.; Pahlevanzade, A.; Panigrahi, P. K.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2021)
Heart failure (HF) demonstrates an epidemic-shaped growth worldwide and continues to be a staggering health problem regardless of unprecedented efforts in diagnosis and treatment. Any phenotype of HF is associated with increased mortality and morbidity, and also draws exaggerated expenditures from the health care system. Conventional biological markers, such as natriuretic peptides, cardiac troponins, are recommended to predict, diagnose, and stratify patients at higher risk of HF, but their discriminative potencies appear to be sufficiently distinguished in patients having HF with reduced and preserved (HFpEF) ejection fraction besides in case of metabolic comorbidities including diabetes mellitus and abdominal obesity. The discovery of new biological markers to improve predictive models is considered a promising approach in shaping patientcentered care of HFpEF when conventional stratification models reveal limited efficacy. The narrative review aims to elucidate the discriminative ability of fetuin-A to improve the predictive value of conventional biomarkers models among patients with overt HFpEF. We found that fetuin-A serves multifaceted functions being simultaneously a promoter of cardiac remodeling, vascular calcification, HF, adipose tissue and systemic inflammation, type 2 diabetes mellitus, metabolic syndrome, and abdominal obesity, and also it exerts tissue-protective effects. Fetuin-A was found to be closely associated with cardiovascular disease and HFpEF and revealed an ability to improve conventional biomarkers’ model to predict HFpEF occurrence.
Keywords: Heart failure; Biomarkers; Fetuin-A; Prediction; Outcomes